Analisis pengaruh profitabilitas, cash flow, dan kebijakan manajemen terhadap opini audit going concern pada perusahaan manufaktur yang terdaftar di bursa efek Indonesia - Yani, Meria; Asmeri, Rina; Andini, Nurul (Jurnal Indovisi, 2018)
The assumption of going concern requires companies operationally has the ability to maintain their life (going concern). If the auditor is not convinced by the company's ability to survivethe auditor should address the issue in the audit report. The purpose of this study to provide evidence of ananalysis of profitabilitycash flow, and management policy of audit opinion going concernThis study focused on manufacturing companies listed in Indonesia Stock Exchange 2011-2015 periodwith the number of observations for 135 sample obtained by purposive sampling method. Technical Analysis of the data used in this study is a technical logistic regression analysis. Based on the analysis found that the variable cashflow and management policy does not significantly influence going concern audit opinion on the companies listed in Indonesia Stock Exchange in 2011-2015.